Editorial. Issue 2 (1st December 2020) - Gardner, Peter R.; Abrams, Benjamin
Abstract : Even amid a global pandemic, contention never ceases. Despite governmental restrictions on public assembly in countries across the globe and the societal fears of transmission, the COVID-19 pandemic has nonetheless been a period of widespread contentious action. The Black Lives Matter protests in the United States sparked a host of antiracist protests worldwide, in the United Kingdom, Spain, Belgium, Ireland, Australia, South Korea, and elsewhere. In May, after a brief lull, the pro-democracy movement in Hong Kong resumed street action. In August, thousands amassed in Minsk to oppose the result of the Belarussian presidential election, alleged by many to be fraudulent. Days later, large crowds of demonstrators gathered in Bangkok calling for reformation of the Thai monarchy and the dissolution of Prayut Chan-O-Cha's government. At the time of writing, the environmentalist group Extinction Rebellion appears poised for mass action in Westminster to call for a political response commensurate with the scale of the climate crisis to be passed into UK legislation. All this is to say that even when societies lock down, opportunities for contention most certainly remain open.